Influence Of Brand Image, Lifestyle, And Product Quality On Iphone Smartphone Purchase Decision - Rizal Rizal; Ahmad Yani (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study aims to determine the brand image, lifestyle, and product quality on the Iphone smartphone purchase decision. The population used in this study were STIE PERTIBA Pangkalpinang students. The method used in this study is a partial test with a Likert scale. The sample in this study were iPhone smartphone consumers with a total of 100 respondents. Statistical tests were carried out using multiple linear regression analysis with SPSS 25 computer program. Validation test using Pearson Product Moment. Meanwhile, the reliability test uses the Cronbach'c alpha value, the classical assumption test. After all the results of the indicator items used in this study are valid and reliable, then the hypothesis is tested. Of the three hypotheses proposed, all of them are supported and for each hypothesis there is one researcher who says the results are not significant. The conclusion of this study is the importance of maintaining a brand image for a better lifestyle and maintaining good product quality, in order to get good consumer reviews, besides that it is also important to pay attention to lifestyle in order to remain confident and make purchasing decisions.